Advances and technical standards in neurosurgery - Pickard, J. D. (Advances and Technical Standards in Neurosurgery, 2012)
Advances: H. Duffau: Subpial dissection and subcortical mapping with vasculature and white matter pathways preservation in surgery for brain (low grade) gliomas. - F. Scholtes, G. Brook, D. Martin: Spinal cord injury and its treatment: current management and experimental perspectives. - M. Sindou, M. Messerer, J. Alvernia, G. Saint-Pierre: Percutaneous Biopsy through the Foramen Ovale for Parasellar lesions: Surgical anatomy, Method and Indications. - Technical Standards: C. Raftopoulos, F. Waterkeyn, E. Fomekong, T. Duprez: Percutaneous pedicle screw implantation with robotic intraoperative 2D/3D fluoroscopy for refractory low back pain. - I. Zemmoura, S. Velut, P. Francois:The choroidal fissure: anatomy and surgical implications. - I. Timofeev, T. Santarius, A.G. Kolias, P.J.A. Hutchinson: Decompressive craniectomy - operative technique and perioperative care. - S Fauser, J Zentner: Management of complex cortical dysplasia in epilepsy